Effect of virtual case-based learning (CBL) using the flipped class and peer instruction on the motivation to learn basic sciences - Maryam Alizadeh; Alireza Saramad; Haniyeh Rafiepoor; Ali Taghvaei; Roya Rayati; Sajjad Sibevei; Zeynab Sarparast Seyyedlar; Sana Peighambardoust; Amirhasan Zomorrodi; Azadeh Angouraj Taghavi (BMC Medical Education)
Abstract Background According to Self-Determination Theory, active learning methods, as alterations to the learning environment, can influence students’ academic motivation to learn. The purpose of this quasi-experimental study was to investigate the effect of virtual case-based learning sessions on the learning motivation of first- and second-year medical students. Methods A total of 258 students, 128in the intervention group and 130 in the control group, were enrolled in the study. The control group consisted of medical students who had not previously participated in virtual case-based learning sessions and were trained in the same curriculum as the intervention group. Two questionnaires were created to evaluate learning motivation in basic science and the motivational outcomes of virtual case-based learning sessions, drawing on the three fundamental needs outlined in Self Determination Theory. The questionnaires were designed through individual interviews with students and validated using Lawshe’s method and Cronbach’s Alpha. The virtual case-based learning sessions were designed as a series of webinars on various topics, with students randomly divided into groups and assigned trained moderators. Clinical scenarios were designed by a team of basic scientists and clinical educators. Each virtual case-based discussion consisted of three phases and was completed in three days. Comparisons between two groups were made using the two-sample t-test and Pearson’s correlation coefficient was used to analyze the motivational consequence questionnaire. Results The results of the study indicated that virtual case-based learning sessions had a significant impact on the learning motivation of basic science students (p < 0.01). Additionally, the most notable motivational consequences of CBL sessions were basic sciences applicability and its interestingness. Conclusions The study provides valuable insights into the effectiveness of virtual case-based learning sessions and suggests avenues for future research. The findings of this study could be useful for educators and institutions seeking to enhance the learning motivation of medical students through virtual case-based learning sessions. However, further research is needed to investigate the long-term effects of virtual case-based learning on student motivation and academic performance.